Analysis of Service Quality on Patient Satisfaction Using the Importance Performance Analysis (IPA) Method (Case Study: UPT Puskesmas Stabat Lama) - Prameli N. M Sinaga; Arnah Ritonga (Formosa Journal of Applied Sciences, 2022)
The Importance Performance Analysis (IPA) method functions as a method to measure and determine patient satisfaction which is considered important by patients and received by patients and prioritizes improving service quality. The use of IPA at UPT Stabat Lama Health Center is to measure the satisfaction of services received by patients. There are 5 dimensions used in this study, namely physical evidence, reliability, responsiveness, assurance, and empathy. This study has 30 valid attributes that are asked of patients. Based on the quadrant analysis, 2 attributes were obtained that needed improvement from the Stabat Lama Health Center UPT. The Wilcoxon Marked Level Test serves to identify differences in the quality of service expected by patients and in reality. Based on these results it was concluded that there was a high difference between the quality of service expected by the patient and the reality, which was 6.292.